The Association Between Pregnant Women’s Knowledge of Triple Elimination and Compliance with Screening Examinations - Sukarni Setya Yuningsih; Ajeng Pratiwi; Heti Fatmawati; Imel Meistika; Irma Mayangsari; Nur Khusnul Khotimah; Rika Rizqillah Muluk; Sumarni (Postgraduate, University of Mataram, 2025)
Knowledge about Triple Elimination, an integrated screening program for HIV, hepatitis B, and syphilis, plays a vital role in improving pregnant women’s adherence to early detection procedures during the first trimester. Strengthening maternal awareness is essential to prevent mother-to-child transmission of these infections. This study aimed to examine the association between pregnant women’s knowledge of Triple Elimination and their compliance with the recommended screening examinations. A quantitative descriptive design with a cross-sectional approach was employed. A total of 350 pregnant women were selected as the study sample. Data were analyzed using the chi-square statistical test to determine the association between knowledge levels and examination compliance. The results showed a significant relationship between knowledge about Triple Elimination and screening compliance (p = 0.000; α = 0.05), indicating that higher levels of maternal knowledge were associated with greater adherence to the recommended tests. This study highlights the importance of strengthening educational strategies to improve maternal knowledge and ensure consistent compliance with Triple Elimination screening. The findings can serve as evidence for policymakers and healthcare providers in designing sustainable interventions to enhance maternal and neonatal health outcomes.